Análisis de la eficiencia de la potestad sancionadora de INDECOPI y de los Colegios de Notarios en la protección del consumidor de servicios notariales - Gutiérrez Guerrero, Miguel (2020)
Today, Peruvian legislation has an exorbitant amount of laws, which is why it is not uncommon to find that in a specific subject there is more than one legislation, precisely this work will be responsible for analyzing why in many cases both Indecopi as an organ supervisor and protector of the rights of consumers, such as the Courts of Honor of the Notary Associations as an organ responsible for verifying the functional conduct of the notary, are empowered to impose sanctions, considering the damage caused to the user; then we will see that currently both instances have sanctioning powers against the notary service providers when the scope of each of them should be clearly defined; I will analyze where the confusion arises, the good and the bad of the norms that regulate the sanctioning aspects, I will describe the cases raised that have generated controversy and finally we will propose how the powers that each of these routes should have should be specified.